Optimization of electric propulsion systems for ferry vessels: a case study in riverine operations (Journal of Naval Architecture and Marine Engineering, 2026)
This study aims to design, optimize, and validate an all-electric propulsion system for a 25 m × 7 m aluminum catamaran ferry operating on a 25 km urban river route, focusing on power requirement prediction, battery sizing, energy-management strategies, and shore-charging integration. A slender-body resistance model, validated by cubic speed–power scaling, predicts calm-water resistance rising from 18.5 kN at 12 knot to 43.8 kN at the contractual speed 19 knot. Accounting for hull and drivetrain efficiencies yields a continuous shaft power requirement of 707 kW. Two 360° Hydromaster D-series azimuth thrusters driven by 375 kW permanent-magnet motors are selected, providing 6 % continuous head-room and full redundancy while avoiding the mass penalty of a single 1 MW unit. Daily energy demand is quantified via a mode-based load matrix distinguishing propulsion, hotel, and intermittent peaks. Twelve round trips within a 17 h duty window consume 16.1 MWh for propulsion and 0.09 MWh for auxiliaries (16.2 MWh total). Limiting depth-of-discharge to 80% and reserving 20% state-of-charge for emergencies yields a 20.3 MWh lithium-iron-phosphate battery bank (204×100 kWh modules; 127 t, 68 m³) fitted amidships. Opportunity charging during each 25 min turnaround with a 6 MW liquid-cooled DC connector restores 1.7 MWh per call, maintaining the pack between 40% and 80% SOC and eliminating the need for 20–48 MW fast-charge infrastructure. This paper applies a Genetic Algorithm (GA) to optimize the decision vector Pthr, Cbat, Pchg, yielding a 12 % reduction in daily energy consumption compared to the baseline design. Convergence behaviour, optimal parameter values, and trade‑offs between energy and capital cost are presented. Load-levelling strategies—radar standby, demand-controlled ventilation, and regenerative braking—trim hotel consumption by up to 15 % and reduce peak inverter currents. Sensitivity analysis shows that lowering service speed to 17 knot cuts daily energy by 23%, highlighting the trade-off between timetable and shore-power investment. By integrating resistance prediction, thruster selection, battery sizing, and charging strategy into a single framework, this research demonstrates the technical and operational feasibility of zero-emission river ferries and provides a repeatable methodology for future deployments in similarly constrained waterways.Journal of Naval Architecture and Marine Engineering, 23(1), 2026, PP. 75-92